Formulation and preclinical studies with a trivalent rotavirus P2-VP8 subunit vaccine - Kyle Lakatos; David McAdams; Jessica A. White; Dexiang Chen (Taylor & Francis Group, 2020)
More effective rotavirus vaccines are essential for preventing extensive diarrheal morbidity and mortality in children under five years of age in low-resource regions. Nonreplicating rotavirus vaccines (NRRV) administered parenterally provide an alternate vaccination method to the current licensed oral vaccine. Live attenuated vaccines and may generate increased efficacy in low-resource settings because the parenteral administration route bypasses some of the challenges associated with oral administration, including differences in intestinal environments. Work described here supports development of a trivalent NRRV vaccine for parenteral administration to avoid complications of the gastrointestinal route. Recombinant VP8* subunit proteins representing some of the most prevalent strains of rotavirus infecting humans - DS-1 (P[4]), 1076 (P[6]), and Wa (P[8]) - were combined with an aluminum adjuvant and the P2 epitope of tetanus toxoid to enhance the immune response to this NRRV antigen. Vaccine formulation development included selection of aluminum hydroxide (Alhydrogel®) as an appropriate adjuvant as well as an optimal buffer to maintain antigen stability and optimize antigen binding to the adjuvant. Characterization assays were used to select the lead vaccine formulation and monitor formulation stability. The NRRV liquid formulation was stable for one year at 2°C to 8°C and four weeks at 37°C. Immunogenicity of the NRRV formulation was evaluated using a guinea pig model, where we demonstrated that the adjuvant provided a 20-fold increase in neutralization titer against a homologous antigen and that the P2-fusion also enhanced the serum neutralizing antibody responses. This vaccine candidate is currently being evaluated in human clinical trials.